EFFECT OF FEDERAL GOVERNMENT EXPENDITURE ON SMALL AND MEDIUM ENTERPRISES DEVELOPMENT IN NIGERIA (Journal of the Management Sciences, 2024)
This study appraised the effect of federal government expenditure on small and medium enterprises development in Nigeria from 1999-2022 using Ordinary Least Square (OLS) technique method. The objectives of the study are to examine impact of government expenditure on small and medium enterprises development in Nigeria, to examine the effect of gross domestic product, government expenditure, unemployment rate, commercial banks credit to SMEs subsector and interest rate on small and medium enterprises output. Secondary data used were obtained from the Statistical Bulletin of Central Bank of Nigeria. OLS techniques was applied after determining stationarity of our variables using the ADF Statistic, as well as the cointegration of variables using the Johansen approach. It was discovered that the variables are stationary and have a long term relationship among the variables in the model. From the result of the OLS, gross domestic product, commercial banks credit to the SMEs and interest rate significantly contribute to SMEs development. It is also observed that gross domestic product, government expenditure and commercial banks credit to SMEs have a positive relationship with SMEs growth and development in Nigeria. On the other hand, unemployment and interest rate have a negative relationship with SMEs. The study recommends that the government should improve all the components part of the real GDP. This will help develop the SMEs subsector. The government should invest more on infrastructure that will enhance the development of SMEs. This is because critical infrastructure like electricity, roads and technology improve business performance and create employment. The government through the apex bank should ensure that adequate credit at reduced interest rate is extended to the SMEs subsector to enable businesses thrive as done in advance countries.
Keywords: GDP, expenditure, unemployment Rate, SMEs, Interest Rate